2007
DOI: 10.1097/01.hp.0000281178.75068.e3
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Following the Chernobyl Accident

Abstract: The accident at the Chernobyl Nuclear Power Plant in Ukraine in 1986 led to a substantial increase of thyroid cancer among those exposed as children. The other cancer that is the most sensitive to the effects of ionizing radiation is leukemia, and this paper evaluates the evidence relating exposure to Chernobyl radioactivity and leukemia risk. Two types of objectives are identified, namely, scientific evidence and public health, and two approaches to addressing such objectives are discussed. Empirical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Most published studies of Chornobyl cleanup workers report an elevated risk of leukemia (1, 4), with much of the evidence coming from studies of Russian cleanup workers who received average doses of 100–200 mGy (5–8). Based on the dose and follow-up information for 168,000 workers from the Russian National Medical and Dosimetric Registry, Ivanov et al (5) reported an increased risk of all leukemia with an ERR of 4.3 per Gy (n=48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published studies of Chornobyl cleanup workers report an elevated risk of leukemia (1, 4), with much of the evidence coming from studies of Russian cleanup workers who received average doses of 100–200 mGy (5–8). Based on the dose and follow-up information for 168,000 workers from the Russian National Medical and Dosimetric Registry, Ivanov et al (5) reported an increased risk of all leukemia with an ERR of 4.3 per Gy (n=48).…”
Section: Discussionmentioning
confidence: 99%
“…The accident at the Chornobyl (Chernobyl) nuclear power plant in northern Ukraine in April 1986, as well as being a public health, social and economic disaster for the countries most affected, also provided an opportunity to evaluate the relationship between leukemia and low dose and low dose-rate radiation (4). After the accident, several hundred thousand workers, who were involved in cleaning up the site and its surroundings, received fractionated whole-body doses, primarily from external radiation (1).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to iodine 131 involves an element of whole-body radiation, as does exposure to other radioactive isotopes, especially cesium. Increases in leukemia incidence in exposed populations have been both claimed and denied; a recent assessment concludes that, apart from cleanup workers, there is no proof of a link to exposure (Howe, 2007). There have been reports, sometimes anecdotal, of increases in a variety of other tumors in those exposed to Chernobyl fallout, including brain and kidney.…”
Section: Nonthyroid Diseasesmentioning
confidence: 99%
“…Cancers, and in particular leukemias seem to represent the most serious effects of the exposure to ionizing radiation. Meanwhile, the question as to whether the incidence of leukemias and malignant lymphomas among 260,807 Ukrainian clean-up workers of 1986 and 43,366 of 1987 (average doses of 14.0 cGy in 1986 and 9.0 cGy in 1987) has increased in the 25 years since the catastrophe is still a point of much controversy [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%